From the past to the future – glacial refugia, current distribution patterns and future potential range changes of Diodonopsis (Orchidaceae) representatives - Kolanowsca, Marta; Rykaczewski, Max (Lankesteriana: International Journal on Orchidology, 2017)
The distribution patterns of Neotropical orchid genus Diodonopsis were analysed and the location of its glacial refugia was reconstructed. The possible changes in the coverage of suitable niches of Diodonopsis representatives were evaluated using three different scenarios. The results of ecological niche modeling indicated that the range of studied taxa is in regression since last glacial maximum. The climatic niches of three Diodonopsis species are well separated.